Kilka refleksji metodycznych o badaniach architektury w historii sztuki - Jarzewicz, Jarosław (Artium Quaestiones, 2025)
The article reviews the current situation and trends in research in the field of the history of architecture. Various research methods are used, including traditional ones, which produce excellent results, and modern ones that have emerged relatively recently due to revolutionary technological progress. Among the latter, the use of modern measurement and analytical techniques that provide new data for interpretation is particularly fruitful. Based on examples of research from the last quarter of a century, excellent progress has been noted in research based on both the latest technologies and those based on the use of updated traditional tools. Modern techniques and methods do not render traditional methods (such as the comparative or genetic method) obsolete, but supplement them by providing substantial new data, which allows them to be used in a more precise way. A collection of many data (observation statements) alone is not an explanation. It should be organized in the form of a theory, statements that answer the basic question: Why is it like this and not different? In the case of art history, this is called interpretation.